2019
DOI: 10.1186/s13058-019-1163-7
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt involution induces inflammation, estrogenic signaling, and hyperplasia linking lack of breastfeeding with increased risk of breast cancer

Abstract: Background A large collaborative analysis of data from 47 epidemiological studies concluded that longer duration of breastfeeding reduces the risk of developing breast cancer. Despite the strong epidemiological evidence, the molecular mechanisms linking prolonged breastfeeding to decreased risk of breast cancer remain poorly understood. Methods We modeled two types of breastfeeding behaviors in wild type FVB/N mice: (1) normal or gradual involution of breast tissue foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…The latter observation in mice that abrupt cessation promoted the expression of estrogen and progesterone receptors is in agreement with the protective effect of breastfeeding against ER+ breast cancer in women (23,37). The authors also reported ductal hyperplasia four months postpartum in mice where lactation was abruptly interrupted (113). It is currently unknown whether this holds true in humans.…”
Section: Mechanistic Insights Into the Protective Effect Of Lactationsupporting
confidence: 65%
See 2 more Smart Citations
“…The latter observation in mice that abrupt cessation promoted the expression of estrogen and progesterone receptors is in agreement with the protective effect of breastfeeding against ER+ breast cancer in women (23,37). The authors also reported ductal hyperplasia four months postpartum in mice where lactation was abruptly interrupted (113). It is currently unknown whether this holds true in humans.…”
Section: Mechanistic Insights Into the Protective Effect Of Lactationsupporting
confidence: 65%
“…This finding is consistent with the role of PAPP-A in involution and the importance of the STCs to inhibit PAPP-A activity, since PAPP-A is known to be induced by inflammatory cytokines such as IL-6, TNF, IL-1, IL-4, and TGF- (112). Abrupt cessation of lactation was also associated with increased cellular proliferation and deposition of collagen as well as expansion of the luminal progenitor cells in the mammary gland compared to mice where cessation of lactation was gradual (113). The latter observation in mice that abrupt cessation promoted the expression of estrogen and progesterone receptors is in agreement with the protective effect of breastfeeding against ER+ breast cancer in women (23,37).…”
Section: Mechanistic Insights Into the Protective Effect Of Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recently published mouse studies, our data showing heightened immune cell infiltrate and cell death in healthy postweaning breast tissue might also be unanticipated. Specifically, in several mouse models, longer duration of lactation and more gradual weaning are found to protect against breast cancer [49][50][51] . These gradual weaning studies suggest that rodent models of abrupt weaning may not mirror the breast involution processes in humans, who may be more likely to participate in gradual weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Inverse associations of aspirin with ER− and TN disease may therefore be driven by its anti-inflammatory effects rather than hormone-dependent mechanisms [ 40 , 41 ]. Indeed, our observation of stronger associations among women 50 years and older, those with higher central adiposity, and parous women, groups with higher levels of systemic inflammation [ 42 46 ], is supportive of this theory; however, we were not able to evaluate potential mechanisms directly in this study.…”
Section: Discussionmentioning
confidence: 69%